Sex of sexual partners and disordered weight control behaviors in a nationally representative sample of South Korean adolescents. (April 2018) - Yu, Kimberly Y.; Kim, Yongjoo; Calzo, Jerel P.; Levinson, Jordan A.; Austin, S. Bryn
Abstract: Eating disorders are a serious and life-threatening health issue associated with physical and mental health problems. Stigma associated with sexual orientation is thought to be one contributor to eating disorders symptoms in U.S. adolescents. Additional research on disordered weight control behaviors in diverse populations is needed to better understand their etiology. To examine the association of sex of sexual partners with disordered weight control behaviors among South Korean adolescents, we analyzed survey data from 67, 266 adolescents, ages 12–18 years, from the 2015 Korea Youth Risk Behavior Web-based Survey. Adolescents were grouped based on self-reported sex of sexual partners. Disordered weight control behaviors included fasting, vomiting, or use of unprescribed diet pills for weight control in the past month. Among both girls and boys, those reporting partners of both sexes had higher odds and those with no sexual partners had lower odds of disordered weight control behaviors. Those with same-sex partners only were not significantly different in disordered weight control behaviors from those with other-sex partners only for girls or boys. Our findings demonstrate the need for further research identifying ways to mitigate risk for this vulnerable group. Highlights: South Korean adolescents with sexual partners of both sexes have elevated odds of disordered weight control behaviors. Among South Korean adolescents, 6.6% of girls and 3.1% of boys report disordered weight control behaviors. South Korean adolescents with only same-sex sexual partners do not have elevated odds of disordered weight control behaviors.